Representasi Anak Muda Gaul dan Saleh dalam Gerakan Hijrah: Analisis Semiotika Roland Barthes atas Konten Akun Instagram Pesan Trend Pemuda (@pesan_trend) - Muhamad Ibtissam Han (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2021)
The stagnation of da'wah among young people is mostly caused by the use of symbols that are not in line with or even contrary to the aspirations of young people. The da'wah offered by the Hijrah Youth Shift Movement is a da'wah that uses symbols of young people as a medium for their da'wah. This article tries to explain how the Hijrah Youth Shift Movement represents the value of young people who are slang and pious. Through Rolland Barthes' semiotic approach, the author tries to examine these symbols which are presented in the da'wah content uploaded to the Instagram @message_trend account. In denotation, posts from the Instagram @message_trend account display activities such as cleaning, archery, camping, tahajud prayer in green open spaces. In connotation, the Instagram account @pesan_trend tries to show a model of young Muslim people who love the environment, are physically and spiritually healthy. Mythically or ideologically, @pesan_trend, which was initiated by UHA and Shift Pemuda Hijrah, is showing the social class of middle-class Muslim youth, which so far has been identified with indie culture, which is active in green spaces. On the other hand, this also shows the ideology of Shift which is leaning towards the tarbiyah movement.